Gerenciamento do Limiar de Desfibrilaçao (DFT Manager) - Lumax 540: Gerenciamento do Limiar de Desfibrilaçao (DFT Manager) - Lumax 540 - Biotronik, (JOURNAL OF CARDIAC ARRHYTHMIAS, 2010)
Espaço publicitário